2004
DOI: 10.2466/pms.98.2.463-472
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blinking Behavior during Listening to and Speaking in Japanese and English

Abstract: Blinking behavior during conversation may be different between conditions in listening and responding to questions because sifting attention from external to internal is possibly associated. The purpose of this study was to compare blinking behavior, duration, heart rates, and mental states during the tasks of listening to and responding to questions in Japanese and English. Participants were 67 (35 men and 32 women) undergraduate students. Blink rate while responding to questions in English did not differ fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…For example, patients with schizophrenia exhibit a higher blink rate, while those with Parkinson’s Disease show a lower blink rate, most likely due to differences in dopamine levels in those conditions [325327]. Cognitive state can also vary the blink rate [328330]. Reading, working on computers, or other visual tasks requiring concentration are known to decrease blink frequency [316,321,324,331,332].…”
Section: Neural Regulation Of Eye Blinksmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, patients with schizophrenia exhibit a higher blink rate, while those with Parkinson’s Disease show a lower blink rate, most likely due to differences in dopamine levels in those conditions [325327]. Cognitive state can also vary the blink rate [328330]. Reading, working on computers, or other visual tasks requiring concentration are known to decrease blink frequency [316,321,324,331,332].…”
Section: Neural Regulation Of Eye Blinksmentioning
confidence: 99%
“…Given the large percentage of the population that works on computers, this is likely to be a major cause of the increasing incidence of ergonomic dry eye complaints. Engaging in conversation and daydreaming can also affect blink rate [328330], so that any clinical measure of blink rate should include information about task and lighting because blink rate varies so widely with mood and task. Time of day should also be included as blink rate is known to vary diurnally, presumably due to changing dopamine levels over the day [333].…”
Section: Evaluation Of Ocular Surface Neurobiologymentioning
confidence: 99%
“…Aside from these protective mechanisms for the cornea, changes in blinking behavior have been shown to occur as a function of non-ocular factors. For example, decreases in blink rates have been associated with memory operations, thinking, and attentive behaviors (Holland and Tarlow, 1975; Hirokawa, et al, 2004). It is well-known that in a number of neurological disorders, such as schizophrenia, Tourette's syndrome, Parkinson's disease, and progressive supranuclear palsy, patients have been reported to show increased blink rates that are thought to be associated with aberrant changes to dopaminergic systems in the brain (Chan and Chen, 2004; Karson, et al, 1984; Swarztrauber and Fujikawa, 1998; Tulen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Crucially for this study, blink behaviour did not give rise to gaze avoidance in East Asian dyads, but we suggest future studies to consider the possibility that blinks could serve as a way to break mutual gaze in a subtle, socially appropriate manner, without a gaze shift away from the face. Although eye blinks are sometimes considered as artefacts that function as a biological mechanism (e.g., to protect the corneal surface; Ousler et al, 2008), blinks have also been linked to cognitive processes (Hirokawa et al, 2004;Holland & Tarlow, 1975) and have been shown to be relevant in social interactions, with longer blinks more likely to occur during mutual gaze (Hömke et al, 2017) highlighting the influence of blink coding on the analysis of social gaze. Dual head-mounted eye-tracking can provide detailed insight into gaze behaviour during dyadic social interactions, but naturally comes with some limitations that need to be acknowledged.…”
Section: Discussionmentioning
confidence: 99%